2002
DOI: 10.1128/cmr.15.2.278-293.2002
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Approach to Malaria Control

Abstract: Malaria draws global attention in a cyclic manner, with interest and associated financing waxing and waning according to political and humanitarian concerns. Currently we are on an upswing, which should be carefully developed. Malaria parasites have been eliminated from Europe and North America through the use of residual insecticides and manipulation of environmental and ecological characteristics; however, in many tropical and some temperate areas the incidence of disease is increasing dramatically. Much of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
114
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(115 citation statements)
references
References 78 publications
1
114
0
Order By: Relevance
“…In Zambia, multiple control interventions, including environmental management against Anopheles larval stages and improvement in hygiene and sanitation reduced the overall malaria incidence and mortality rates by approximately 50% [4]. In Europe and North America, malaria was eliminated through use of insecticides and manipulation of the environment [5]. Preliminary studies in Bolifamba indicate that malaria transmission is perennial [6] with Anopheles mosquitoes occurring throughout the year.…”
Section: Introductionmentioning
confidence: 99%
“…In Zambia, multiple control interventions, including environmental management against Anopheles larval stages and improvement in hygiene and sanitation reduced the overall malaria incidence and mortality rates by approximately 50% [4]. In Europe and North America, malaria was eliminated through use of insecticides and manipulation of the environment [5]. Preliminary studies in Bolifamba indicate that malaria transmission is perennial [6] with Anopheles mosquitoes occurring throughout the year.…”
Section: Introductionmentioning
confidence: 99%
“…Plasmodium parasites responsible for human malaria are obligately dependent on mosquitoes of the genus Anopheles for transmission from one human host to the next, with Anopheles gambiae being the primary vector in Africa (8). There is no vaccine currently available for malaria treatment, and therefore, control of the disease is limited to antiparasitic drugs and control of the mosquito vectors (2,22). Control of the disease has been hampered by evolution of drug resistance in Plasmodium species (25), evolution of insecticide resistance in the mosquito vectors (12), and lack of basic public health infrastructure to sustain vector control efforts in problem areas (6,26).…”
mentioning
confidence: 99%
“…The disease infected approximately 200 to 300 million people each year and the mortality rate was approximately 3 million per annum [8,9]. Statistics for the year 2010 indicated that almost half the population of the world, which was 3.3 billion people, could have fallen prey to malaria.…”
Section: Review Workmentioning
confidence: 99%